Learning through blogging - Sujud, Arba'ie; Abd Rahim, Normaliza (American-Eurasian Network for Scientific Information, 2013)
Blog is an online diaries or journal for individuals who loves writing and as business entries for companies or individual in running business. It has been widely used since it can be published in the website for free. The objectives of the study were to identify and discuss the use of blog writing from the perspective of Korean learners learning the Malay language as a foreign language. The samples of the study consist of 60 male and female volunteered subjects from six classes of Malay language. The subjects had the experience in writing in the blog from the previous semester. The subjects were given a set of questionnaire and interviewed based on their opinions on blog learning. The results of the study revealed that more than 80% of the female subjects while more than 65% of the male subjects stated that they wrote in the blog for literature, language and multimedia learning. The results also revealed that all the subjects had increase in motivation and confidence in writing specifically in the Malay language. It is hoped that future research will focus on other technology to enhance writing in the second language.